Estudos de compatibilidade dos fármacos fenofibrato, ciprofibrato e citalopram com alguns excipientes - Sumaia Araújo Pires (2016)
In order to assess possible existing interactions of ciprofibrate, fenofibrate and citalopram drugs with the commonly used excipients in commercial formulations, each (1:1 m/m) binary mixtures were evaluated by Differential Scanning Calorimetry (DSC), X-ray Powder Diffraction (XRPD), Fourier Transform Infrared Spectroscopy (FTIR) and Solid State Nuclear Magnetic Resonance (ssNMR). The excipients studied were starch, microcrystalline cellulose, crospovidone, magnesium stearate, hydroxyl propyl methylcellulose, lactose monohydrate and sodium lauryl sulfate. The binaries for citalopram has shown no evidences of any interaction by DSC, nevertheless, blending it with lactose show visible changes in the thermal behavior profile. However, ciprofibrate have presented a possible interaction with hydroxylpropylmethylcellulose and fenofibrate with magnesium stearate. The FTER. compatibility study of ciprofibrate has shown no spectrum change for its binaries, the only observable effect was on the binary of fenofibrate with magnesium stearate. The ssNMR analyses did not indicate chemical interactions between citalopram and the chosen excipients. XRPD show that those excipients do not alter the crystalline form of the drugs fenofibrate, ciprofibrate and citalopram in (1:1 m/m) binary mixtures.